The effect of different teaching condition in kinematic parameters on learning a gymnastic skill on the high bar - Dallas, G.; Kirialanis, P.; Kaimakamis, V. (Serbian Journal of Sports Sciences, 2008)
This study examines the effects of implementing different instruction strategies with the use of visual observation, physical guidance and kinematic information as feedback, and presents the differentiation of kinematic parameters in learning and retention of learning a complex gymnastic skill on the high bar. Eighty-four (84) undergraduate students were assigned to four groups that had an equal practice schedule. Group 1 observed other participants' personal presentations (O), Group 2 observed other participants' performance and received kinematic information feedback (KFb), Group 3 observed the performance and received additional physical guidance plus kinematic information (PhG.+KFb), and Group 4 observed the performance and received additional physical guidance (PhG). The subjects participated in the kip action on the high bar for six days, every second day, and performed 12 trials in every session. The MANOVA model with repeated measures was applied, followed by a Univariate ANOVA model for each dependent variable separately. In each case the group, the measurement, as well as the group • measurement interaction effect was examined. According to the results, the measurement effect was not significant, while there was as overall significant group effect which was further qualified by a significant group • measurement interaction effect. The mean values for the total score of the four groups at the two measurements show the absence of any significant measurement effect. Conversely, there were significant differences between the four groups, where groups three and four scored significantly higher than groups one and two. Also, there was a significant group effect in temporal and spatial parameters in the two measurements. In practically all the cases statistically significant differences involved the differences mainly between Group 3 and the other groups. It was concluded that the combination of physical guidance and kinematic information feedback led to higher scores in this complex gymnastic skill.